1980
DOI: 10.1128/jb.143.3.1444-1449.1980
|View full text |Cite
|
Sign up to set email alerts
|

Generalized transduction in the enterobacterial phytopathogen Erwinia chrysanthemi

Abstract: Bacteriophages induced by mitomycin treatment of Erwinia chrysanthemi KS612 produced plaques on lawns of E. chrysanthemi EC183 and KS605. Bacteriophage Erch-12, purified from one such plaque, transferred an array of chromosomal genes (arg, leu, his, ser, thr, trp, ura) to appropriate recipient strains derived from E. chrysanthemi EC183. Recombinants were formed in the absence of cellular contact between donor and recipient bacteria and in the presence of deoxyribonuclease. Ultraviolet irradiation of the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…and used to study different aspects of the hosts, viz. bacterial cell wall structure (Expert & Toussaint, 1985), generalized transduction (Chatterjee & Brown, 1980), phage typing (Gross et al, 1991) and to estimate bacterial populations in complex environments (Suzuki & Togashi, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…and used to study different aspects of the hosts, viz. bacterial cell wall structure (Expert & Toussaint, 1985), generalized transduction (Chatterjee & Brown, 1980), phage typing (Gross et al, 1991) and to estimate bacterial populations in complex environments (Suzuki & Togashi, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…However, various authors have used genetic approaches to elucidate pathogenic mechanisms in this bacterium and numerous genetic tools have been developed. There have been reports on genetic transfer by transformation (Reverchon and Robert-Baudouy, 1985;Hinton ef ai., 1985) and generalized transduction (Chatterjee and Brown, 1980;Resiboisefa/., 1984) as well as conjugation; various authors showed that the E. ciirysanthemi cells do not appear to exchange chromosomal DNA on their own but will act as conjugal donors if an F-factor or R-factor plasmid is present (Chatterjee and Starr, 1977;Chatterjee, 1980;Kotoujansky etai., 1982;Schoonejans and Toussaint, 1983;Chatterjee ef ai., 1985). Despite all these studies, no precise linkage map of a soft-rotting Erwinia has yet been described (about ten markers have been analysed on each strain).…”
Section: Introductionmentioning
confidence: 99%
“…AC6070 is a spontaneous streptomycin-resistant derivative of AC6022 (his-3 leu-2 arg-i ilv-1) which was obtained by ethyl methanesulfonate mutagenesis of AC6017 (arg-I leu-2 ilv-l) (4).…”
Section: Carotovora Ecc193 Ac401mentioning
confidence: 99%